Spin, charge, and orbital correlations in the one-dimensional t2g -orbital Hubbard model - Xavier, J. C. [UNESP]; Onishi, H.; Hotta, T.; Dagotto, E. (American Physical Society (APS), 2006)
We present the zero-temperature phase diagram of the one-dimensional t2g -orbital Hubbard model, obtained using the density-matrix renormalization group and Lanczos techniques. Emphasis is given to the case of the electron density n=5 corresponding to five electrons per site, while several other cases for electron densities between n=3 and 6 are also studied. At n=5, our results indicate a first-order transition between a paramagnetic (PM) insulator phase, with power-law slowly decaying correlations, and a fully polarized ferromagnetic (FM) state by tuning the Hund's coupling. The results also suggest a transition from the n=5 PM insulator phase to a metallic regime by changing the electron density, either via hole or electron doping. The behavior of the spin, charge, and orbital correlation functions in the FM and PM states are also described in the text and discussed. The robustness of these two states against varying parameters suggests that they may be of relevance in quasi-one-dimensional Co-oxide materials, or even in higher dimensional cobaltite systems as well. © 2006 The American Physical Society.